Mapping the Memory of Armed Conflict through Cancer in Gabriela Ybarra’s El comensal and Héctor Abad Faciolince’s El olvido que seremos - Hunt, Mai (Revista Canadiense de Estudios Hispánicos)

(untitled) (Asociación Canadiense de Hispanistas, 2021)
This study examines how Spanish author Gabriela Ybarra and Colombian Héctor Abad Faciolince tackle the parallel deaths of family members due to cancer and to the violence of armed conflict in their autobiographical novels El comensal (Spain, 2015) and El olvido que seremos (Colombia, 2006), respectively. Looking beyond the trope of cancer as metaphor, Ybarra and Abad Faciolince employ medical language to articulate the intergenerational mysteries surrounding instances of untimely death within their families. Cancer, thus, moves beyond a metaphor for violence and destruction, becoming a mode of representation for studying and articulating the unknown.